Coping with Challenges of Public-Private Partnership (PPP) for Housing Delivery in Nigeria - Muhammad, Zayyanu; Johar, Foziah; ., . (International Journal of Engineering and Technology, 2018)
Although public-private partnerships continue to gain popularity in infrastructure provision, the application of the strategy in housing delivery is bedevilled with many challenges particularly in the context of developing countries like Nigeria. This article aims to offer solutions to the challenges of PPP for housing delivery in Nigeria. Using a case study approach, the article investigated the challenges of PPP housing project in the federal capital territory [FCT] Abuja, Nigeria. The study found that â€œlack of transparency in the procurement processâ€, â€œinappropriate risk allocationâ€, â€œpoor administrative machineryâ€, â€œcorruptionâ€, and incompetent private sectorâ€ are the major challenges that militate against successful housing delivery through public-private partnership in Nigeria. In conclusion, the paper outlined solutions for coping with the challenges of PPP for housing delivery in Nigeria.Â Â